Membaca Teks Hadis: Antara Makna Literal Dan Pesan Utama - Miftahul Huda (Ulumuna, 2007)
Studies on hadîts are very significant to Muslim since it is the second resource of Islam precepts after al-Qur’an. It appears that the main ideas implied in hadîts texts are not as clear as their literal meaning because they, to some extent, were “produced” by history. There are socio-historical factors and hermeneutics influencing the process of producing texts. To understand hadîts texts properly, we need to appreciate these factors as well as their main idea. So, we need to: (1) pay attention to the mission of the prophet and Islam precept, (2) study on social context of Prophet Muhammad era and before, (3) analyze the implication of implementing their main idea, (4) analyze special event related to the creation of hadits, (5) aware about creation of hadîts and its transmission. Considering these five aspects will help us to uncover the wide meaning of hadîts texts, explain their central themes, moral ideas, and relevance to human life.